Osseous-Tissue Tumor Reporting and Data System With Diffusion-Weighted Imaging of Bone Tumors—An Interreader Analysis and Whether It Adds Incremental Value on Tumor Grading Over Conventional Magnetic Resonance Imaging. Issue 2 (7th March 2023) - Guirguis, Mina; Gupta, Anurag; Thakur, Uma; Pezeshk, Parham; Weatherall, Paul; Sharan, Gaurav; Xi, Yin; Chhabra, Avneesh
Abstract : Objective: The aim of the study is to determine whether the use of diffusion-weighted imaging (DWI) provides incremental increase in performance in the osseous-tissue tumor reporting and data system (OT-RADS) with the hypothesis that use of DWI improves interreader agreement and diagnostic accuracy. Methods: In this multireader cross-sectional validation study, multiple musculoskeletal radiologists reviewed osseous tumors with DW images and apparent diffusion coefficient maps. Four blinded readers categorized each lesion using the OT-RADS categorizations. Intraclass correlation (ICC) and Conger κ were used. Diagnostic performance measures including area under the receiver operating curve were reported. These measures were then compared with the previously published work that validated OT-RADS but did not include incremental value assessment of DWI. Results: One hundred thirty-three osseous tumors of the upper and lower extremities (76 benign, 57 malignant) were tested. Interreader agreement for OT-RADS with DWI (ICC = 0.69) was slightly lower (not statistically different) from the previously published work that did not incorporate DWI (ICC = 0.78, P > 0.05). The mean sensitivity, specificity, positive predictive value, negative predictive value, and area under the receiver operating curve including DWI of the 4 readers were 0.80, 0.95, 0.96, 0.79, and 0.91, respectively. In the previously published work without DWI, the mean values of the readers were 0.96, 0.79, 0.78, 0.96, and 0.94, respectively. Conclusions: The addition of DWI to the OT-RADS system does not allow significantly improved area under the curve diagnostic performance measure. Conventional magnetic resonance imaging can be prudently used for OT-RADS for reliable and accurate characterization of bone tumors.